ANALYSIS OF FACTORS THAT INFLUENCE THE INTEREST OF BUYING CONSUMERS AT STICKY RICE MILK (TANSU) STALL IN ENGLISH VILLAGE PARE KEDIRI - Stevanus Gatot Supriyadi; Nabilla Yuansa Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
The purpose of this study is to determine the effect of factors in making a purchasing decision. The number of samples in this study were 45 samples. The analytical tool used is multiple linear regression. The results showed that Cultural Factors partially had a positive and significant effect on consumers' buying interest in the English village rice milk stall pare. The social factors partially have a positive and significant effect on consumer buying interest in the English village milk stick stall. Personal factors partially have no significant effect on consumers' buying interest in the English village rice milk stall pare. Cultural, social and personal factors have a simultaneous effect on consumers' buying interest in milk-stick stalls in the English village of Pare. Keywords: cultural factors, social factors, personal factors, decision factors